Molecular detection of zoonotical Giardia duodenalis, Cryptosporidium spp. and Blastocystis in wild mesocarnivores from Eastern Spain - Martí-Marco, Alba; Moratal, Samantha; Torres-Blas, Irene; Cardells, Jesús; Lizana, Víctor; Dea-Ayuela, María Auxiliadora (Frontiers in Veterinary Science, 2026)
IntroductionChanges in land use and urbanization have altered the distribution and behaviour patterns of wildlife, increasing contacts between people and wild carnivores, elevating the risk of disease transmission. Evidence of enteric parasite presence in wild mesocarnivores from Spain is scarce, particularly in the eastern region.MethodsWe surveyed 221 fecal samples collected in 2018–2023 from nine mesocarnivore species across 85 municipalities in the Valencian Community (eastern Spain). Molecular assays were used to detect Giardia duodenalis, Cryptosporidium spp, and Blastocystis, and positives were characterized by genetic sequencing when possible.ResultsOverall prevalences were 6.8 % for G. duodenalis and for Cryptosporidium (15 of 221), and 8.6 % for Blastocystis (19 of 221). G. duodenalis was detected in seven of nine species, Cryptosporidium in four, and Blastocystis in six. Co-infections occurred but any sample harbored all three parasites. Sequencing revealed multiple Cryptosporidium species with relevance for humans and wildlife (including C. meleagridis, C. canis, C. ditrichi, C. erinacei, C. muris, and C. sp mouse genotype II), and Blastocystis subtypes 3, 4, 5, 6, 7, and 15 in several hosts. As in other studies, genotyping of G. duodenalis was unsuccessful.DiscussionDetection of prey-associated Cryptosporidium in predators supports trophic transmission. The presence of those zoonotic enteroparasites in wild mesocarnivores highlight the need for integrated wildlife and public health surveillance at the human–wildlife interface and for further work to resolve parasite sources, transmission pathways, and the conditions that facilitate cross-species spread.